Tracheal laceration with massive subcutaneous emphysema: a rare complication of endotracheal intubation. - Orta, D A (1979)
Our patient sustained a laceration of the membranous portion of the trachea associated with massive subcutaneous emphysema after an apparently uneventful intubation. The patient was successfully operated on within seven hours. The importance of prompt diagnosis and treatment in the event of this rare complicatoin and the different causative factors are discussed.